Power quantities calculation by using an FPGA device, applying IEEE 1459-2010 standard - De Oro Arenas, Luis [UNESP]; Melo, Guilherme A. E [UNESP]; Canesin, Carlos A. [UNESP] (My University, 2018)
This paper presents the description of an electrical power measurement equipment using an calculation unit embbeded in FPGA. It was developed with the purpose of analyzing 4-wire three-phase systems according to the IEEE 1459-2010 standard, under sinusoidal, non-sinusoidal, balanced and/or unbalanced condition. The modules synthesized in the programmable logic device (PLD) are fully implemented in a hardware description language (HDL) applying digital signal processing techniques for sincronism and fundamental component extraction. Lastly, experimental results for 4-wire three-phase power systems in several scenarios are presented.
Keywords: FPGA devices; IEEE 1459-2010; Power measurement; Power quality; Smart meters